2016
DOI: 10.5194/isprsarchives-xli-b3-769-2016
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Approach for Stitching of Aerial Images

Abstract: ABSTRACT:The last few years have witnessed an increasing volume of aerial image data because of the extensive improvements of the Unmanned Aerial Vehicles (UAVs). These newly developed UAVs have led to a wide variety of applications. A fast assessment of the achieved coverage and overlap of the acquired images of a UAV flight mission is of great help to save the time and cost of the further steps. A fast automatic stitching of the acquired images can help to visually assess the achieved coverage and overlap du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This is to avoid unnecessary computations on nonoverlapping image pairs. To achieve this, exterior orientation parameter (EOP)-based methods [14,20], the Delaunay triangulation-based method [13], and a graph-based method [21] can be used. From among them, we employed the EOP-based method using data obtained by a global positioning system/inertial navigation system mounted on a UAV.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is to avoid unnecessary computations on nonoverlapping image pairs. To achieve this, exterior orientation parameter (EOP)-based methods [14,20], the Delaunay triangulation-based method [13], and a graph-based method [21] can be used. From among them, we employed the EOP-based method using data obtained by a global positioning system/inertial navigation system mounted on a UAV.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…However, this may not take into account the imaging characteristics of small UAVs that are sensitive to environmental changes. Accordingly, the existing methods may determine a relatively tilted image as a mosaic plane [9,13]. This concern was actually realized, as shown in Figure 13a,b.…”
Section: Mosaicking Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the generation of orthomosaics is time-consuming and cannot satisfy the demand of real-time crop growth monitoring. With the purpose of real-time applications, previous researchers found that mosaicking with a proper strategy is very efficient in crop growth monitoring [65,66]. Moreover, image stitching is recommended for a small field, when the terrain is sufficiently flat [67].…”
Section: The Use Of Mosaics or Orthomosaics In Crop Growth Monitoringmentioning
confidence: 99%